Pengaruh Kepemimpinan, Kompetensi dan Disiplin Pegawai terhadap Kinerja Pegawai di Dinas Kesehatan Provinsi Maluku - Patricya Sintya Nanlohy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the influence of Leadership, Competence and Work Discipline on Employee Performance. The population in this study was 119 employees of the Maluku Provincial Health Office. The number of samples used in this study amounted to 54 employees obtained by the Proportional Random Sampling technique. Data collection techniques in this study are questionnaires and documentation studies. Data analysis method using multiple linear regression analysis, hypothesis testing using T Test and F Test is done with the help of SPSS Version 20 for Windows program. The results showed that the leadership variable had a positive and significant effect on employee performance with a calculated t value of 2.667 > t table 1.675 and a significance of 0.004 < 0.05, the competency variable had a positive and significant effect on employee performance with a calculated t value of 3.553 > t table 1.675 and a significance of 0.0001 < 0.05, and the work discipline variable had a positive and significant effect on employee performance with a calculated t value of 6.406 > t table 1.675 with significance of 0.000 < 0.05, so H1, H2, and H3 are accepted. Keywords: Leadership, Competence, Work Discipline and Performance